PEMANFAATAN DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN BAGI UMKM MITRA BINAAN PT.KILANG PERTAMINA INTERNASIONAL REFINERY UNIT III PLAJU PALEMBANG - Kertarajasa, Astro Yudha; Mutiara Lusiana Annisa; Chyntia Ambar Wulan; Seli Lediana; Siti Nur Aisah (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
MSMEs have contributed to gross domestic product in recent years. The use of information technology as a medium in developing its market is an opportunity for MSMEs. Digital marketing is one of the media that is often used by business people. With digital marketing, communications and transactions can be carried out in real time and can be accessed throughout the world, most information about products is available on the internet, it is easy to order and the ability of consumers to compare one product with another. Thus, the aim of community service is to increase understanding regarding the use of digital marketing in order to increase sales for MSMEs. The digital marketing discussed is related to Facebook Ads. In this service, the service partner is PT. Kilang Pertamina Internasional Refinery Unit III Plaju, Palembang City. The method used in this service is in the form of delivering material about the benefits of digital marketing for MSMEs. Special attention before implementing digital marketing, there are still obstacles, for example sales that experience sales fluctuations and unstable sales values ​​for MSMEs. After the presentation of the material, it was continued with a question and answer discussion between the community service team and partners.